Peran Kepuasan Kerja Sebagai Variabel Mediasi Pada Bank X di Kota Surabaya - Surya Andini, Widya; Prima Rini, Hesty; Evanthi, Ayundha (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2025)
Employees are an aspect that has a role in the sustainability of an organization caused by many factors. This study aims to examine the effect of work overload, work life balance on employee performance with the mediation variable of Bank X employee satisfaction in the city of Surabaya. Quantitative methods were used for 40 respondents obtained from saturated sampling techniques as well as data analysis and hypothesis tests using the SEM-PLS method. The results of the analysis indicate that work overload does not contribute to employee performance but can be the cause of increased job satisfaction, work life balance can contribute to increased employee performance and job satisfaction, and job satisfaction can play a role as a mediator of work overload and work life balance in employee performance.